1999
DOI: 10.1002/(sici)1096-9896(199909)189:1<79::aid-path366>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of clonality of sporadic angiomyolipoma

Abstract: Angiomyolipoma, which consists of three intimately intermixed components, smooth muscle, blood vessels, and adipose tissue, is variably considered a hamartoma, a choristoma or a true neoplasm. This study has investigated the clonality of sporadic angiomyolipomas in seven women, each with a single lesion, by determining the pattern of X‐chromosome inactivation. Polymerase chain reaction (PCR) amplification of the highly polymorphic human androgen receptor gene (HUMARA) was performed on the DNA extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Renal AML have already been proven to be monoclonal neoplasms. 3,4 Loss of heterozygosity in the region of the tuberous sclerosis genes TSC1 (9q24) or TSC2 (16p13.3) has been shown in AML and several other "hamartomas" of TSC patients. 5,6 Malignant AML of the kidney have been described in exceptional cases.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Renal AML have already been proven to be monoclonal neoplasms. 3,4 Loss of heterozygosity in the region of the tuberous sclerosis genes TSC1 (9q24) or TSC2 (16p13.3) has been shown in AML and several other "hamartomas" of TSC patients. 5,6 Malignant AML of the kidney have been described in exceptional cases.…”
supporting
confidence: 53%
“…The strong evidence for monoclonality not only in the monophasic tumors but also in one case with polyphasic cellularity supports the hypothesis of clonal proliferation of an uncommitted stem cell, able to evolve towards different cell types already suspected in renal AML. 3,4 One of our cases revealed identical X-chromosomal inactivation patterns in each of 5 separate intrahepatic nodules. This finding points to an intrahepatic spread probably representing metastasis of a single primary tumor.…”
Section: Resultsmentioning
confidence: 99%
“…AMLs have been regarded as hamartomas; however, clonality assays performed in a recent study of renal AMLs has shown the myoid and the vascular components to be monoclonal, implying a neoplastic proliferation (15,16). The adipose tissue component of the AML was found to be polyclonal and the authors speculate that the fat is metaplastic or a reactive change in the neoplasm.…”
Section: Discussionmentioning
confidence: 97%
“…Genetic analyses of sporadic AMLs have demonstrated that these tumors are clonally derived, but the studies have not provided consistent results with respect to an underlying genetic mechanism [27][28][29] . Trisomy 7 has been independently reported in sporadic AMLs.…”
Section: Discussionmentioning
confidence: 99%